The impact of national ICT qualification systems on companies' recruitment practices: an Anglo-German comparison - Hilary Steedman; Karin Wagner (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2007)
The aim of this study is to analyse and assess the contrasting national skills policies associated with ICT (Information and Communication Technologies) skill supply in Britain and Germany. We also aim to examine the impact of these strategies on firms and to assess the utilization of skills at different qualification levels in companies. Finally we point to possible implications for companies, young people and educational institutions of a change in German higher education to the Bachelor degree. The study is based on published statistical sources and on interviews with some 90 firms in Britain and Germany. These were drawn from four sectors, financial services, retailing, motor manufacture and software development.
Keywords: 330; Finanzwirtschaft; Handel; Automobilindustrie; Informationswirtschaft; Betrieb; Personalpolitik; Personaleinstellung - internationaler Vergleich; Informatiker; Fachkräfte; Hochqualifizierte; informationstechnische Bildung; Hochschulbildung; Hochschulsystem - Reform; Bachelor; Berufsbildungssystem; Bildungsökonomie; Bundesrepublik Deutschland; Großbritannien